Deep-fried sweetpotato chip production: a review on pretreatment, frying conditions, and quality parameters - Teshome Ayele, Abebe; Ismail-Fitry, Mohammad Rashedi; Desta Bizualem, Yonas; Kumar, Pavan; Mirete Deresa, Ebisa; Stanley, Nwankwo Chibuzo (Elsevier, 2025)
Fried sweetpotato chips are a snack food made by thinly slicing sweetpotatoes and frying them until they're crispy and golden brown. Dehydrated fried sweetpotato chips are produced mainly by deep-fat frying. The frying process consists of interaction between oil and food at a suitable temperature above 100 °C, leading to various physical, chemical, and sensory attributes changes in the end product, such as starch gelatinization, coloration, and oil absorption. To obtain the acceptable quality of sweetpotato chips with desirable physicochemical, organoleptic quality characteristics like taste, aroma, light color, and crispy/crunchy texture with less oil intake and maximum water loss, parameters of frying and pretreatment (blanching and drying) conditions particularly time and temperature have been studied. This review covers the processing conditions, particularly pretreatment and frying parameters and other processing parameters considered during the production of deep-fried sweetpotato chips and their effects on some physicochemical and organoleptic quality attributes of the finished fried product.